Tingkat Kesuburan Perairan pada Zona Litoral di Waduk Sei Pulai, Pulau Bintan, Kepulauan Riau - Yoga Oktaliandi Saputra; Tri Apriadi; Winny Retna Melani (Majalah Ilmiah Biologi BIOSFERA: A Scientific Journal, 2020)
Sei Pulai Reservoir have been used as water supply for local communities in Tanjungpinang City and surrounding areas. The objective of this study was to determine trophic level in litoral zone of Sei Pulai Reservoir, Bintan Island. Samples were taken by purposive sampling method that represented inlet (Stations 1, 2, 3, 4, and 5); the middle of the reservoir (Station 6,7, 8); and  outlet (Station 9 and 10). The data were analyzed by TLI (Trophic Level Index).  The result of this study showed that the TLI index of inlet, middle, and outlet of Sei Pulai Reservoir were 3.62, 3.30, and 3.60 respectively. Litoral zone of Sei Pulai Reservoir were mesotrophic, with catagorized fair water quality  (moderate amount of nutrient concentration and primary productivity). Water quality are quite good for drinking water.